2021
DOI: 10.1016/j.clnu.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prolonged sitting and physical activity breaks on cognitive performance, perceivable benefits, and cardiometabolic health in overweight/obese adults: The role of meal composition

Abstract: Background & aims: Physical activity (PA) breaks may effectively attenuate the detrimental impact of prolonged sitting on acute cognitive performance, perceivable benefits (e.g. mood), vascular function, and metabolic health. To date, the impact of meal composition on the effects of sedentary behavior and/ or PA breaks on health has been scarcely studied. Therefore, our aim was to investigate whether meal composition alters how sedentary behavior and PA breaks affect these acute health outcomes. Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 57 publications
1
22
2
1
Order By: Relevance
“…However, during the INT trial, leg fidgeting for 1 min on/4 min off improved completion time by 13%, decreased the number of errors by 47% and participants felt 6% less fatigued compared to baseline. Our results build upon those of Wanders, Cuijpers, et al [38] who found that after 4-h of sitting with different Western meal types, physical activity interruption delayed post-breakfast mood and vigour decrements, as well as increases in fatigue and sleepiness irrespective of meal type. However, our findings are also in direct conflict to others [3] who assessed the effects of a high and low glycaemic beverage on TMT B pre and post 180 min of uninterrupted sitting.…”
Section: Comparison To the Literaturesupporting
confidence: 89%
“…However, during the INT trial, leg fidgeting for 1 min on/4 min off improved completion time by 13%, decreased the number of errors by 47% and participants felt 6% less fatigued compared to baseline. Our results build upon those of Wanders, Cuijpers, et al [38] who found that after 4-h of sitting with different Western meal types, physical activity interruption delayed post-breakfast mood and vigour decrements, as well as increases in fatigue and sleepiness irrespective of meal type. However, our findings are also in direct conflict to others [3] who assessed the effects of a high and low glycaemic beverage on TMT B pre and post 180 min of uninterrupted sitting.…”
Section: Comparison To the Literaturesupporting
confidence: 89%
“…Cognitive performance was assessed at two time points across the four days. In contrast to the previous studies, significant effects were not found for cognitive performance after breaking up sitting with cycling 37) . Similar to the walking intervention 35) , the study by Wanders et al 37) reported benefits in mood and other subjective and self-assessed tests 37) .…”
Section: Cycle Desk Interventionscontrasting
confidence: 99%
“…In contrast to the previous studies, significant effects were not found for cognitive performance after breaking up sitting with cycling 37) . Similar to the walking intervention 35) , the study by Wanders et al 37) reported benefits in mood and other subjective and self-assessed tests 37) . This study also reported lower subjective levels of sleepiness, increased self-assessed levels of mood (vigour) and lower selfassessed fatigue levels after cycling 21) .…”
Section: Cycle Desk Interventionscontrasting
confidence: 99%
“…2 . For studies using a device for measurement of sedentary behaviour time, there were 12 studies assessing cognitive flexibility [ 40 42 , 44 , 50 , 51 , 53 , 54 , 58 , 64 66 ], 16 studies for episodic memory [ 47 , 50 , 53 , 54 , 58 , 59 , 61 , 62 , 65 72 ], 11 studies for executive function [ 40 , 50 , 53 , 54 , 58 , 59 , 62 , 66 , 71 73 ], 16 studies for global cognitive function [ 35 37 , 47 , 53 55 , 57 , 60 , 63 , 67 , 74 78 ], three studies reporting on the domain of motor skills and construction [ 35 , 56 , 72 ], 20 studies for processing speed [ 35 , 40 , 41 , 41 , 47 , 50 , 51 , 53 , 54 , 56 , 58 , 59 , 62 , 65 69 , 71 , 72 , 79 ] and 15 for working memory [ 40 …”
Section: Resultsmentioning
confidence: 99%
“…2. For studies using a device for measurement of sedentary behaviour time, there were 12 studies assessing cognitive flexibility [40-42, 44, 50, 51, 53, 54, 58, 64-66], 16 studies for episodic memory [47,50,53,54,58,59,61,62,[65][66][67][68][69][70][71][72], 11 studies for executive function [40,50,53,54,58,59,62,66,[71][72][73], 16 studies for global cognitive function [35-37, 47, 53-55, 57, 60, 63, 67, 74-78], three studies reporting on the domain of motor skills and construction [35,56,72], 20 studies for processing speed [35, 40, 41, 41, 47, 50, 51, 53, 54, 56, 58, 59, 62, 65-69, 71, 72, 79] and 15 for working memory [40-42, 50, 51, 53, 54, 58, 62, 64-66, 70, 72, 73]. For studies using self-report to measure sedentary behaviour time, there were two studies for cognitive flexibility [49,51], five studies for episodic memory [43,47,49,80,81], seven for global cognitive function…”
Section: Association Of Total Sedentary Time With Cognitive Function ...mentioning
confidence: 99%